Weather risks, crop losses, and risk proneness: An examination of evolving risk preferences of rice farmers in Bangladesh - Parker Wheatley, W.; Khanam, Taznoore; Pede, Valerien O.; Yamano, Takashi (Elsevier, 2024)
Changing climate poses significant challenges for smallholder rice farmers. Weather-related deviations from longer-term patterns and crop losses due to abiotic hazards can affect farmer risk preferences and drive adaptive responses. In addition, farmers’ proneness to and past experiences with crop risks such as drought, submergence, and excess soil salinity can impact their baseline risk preferences and their response to changing risks. Using data for Bangladesh from two waves of the Rice Monitoring Survey, climate-related data (precipitation and temperature), farmer reports of crop losses, and measures of proneness to abiotic risks, this article estimates how weather deviations from longer-term trends, crop losses, and proneness to crop risks (submergence, drought, and soil salinity) affect elicited risk preferences over time. This research finds evidence in favor of the hypothesis that larger absolute seasonal deviations from past patterns of seasonal mean daily minimum temperature and seasonal total precipitation yield increased risk aversion. In addition, the research provides mixed evidence with respect to risk proneness and farmers’ change in risk preferences over time. Contrary to our original hypothesis, individuals with land more prone to soil salinity become more risk averse rather than less, but, consistent with our hypothesis, those with land more prone to crop submergence become more risk preferring over time. Because of differences in crop experiences and degrees of proneness to risk, risk preferences for farmers in different regions are predicted to evolve along different pathways. This article contributes to the literature on risk preference formation by considering the possibility that less significant deviations than shocks might also contribute to evolving risk preferences. In addition, the article emphasizes the regional heterogeneity of changing preferences. An ancillary finding of this work suggests that risk preferences are only weakly related over time, contrary to other findings in the literature on the stability of risk preferences. Of policy relevance, the differential experiences in weather variability at the regional and local levels yield important differences in changes in preferences and should give rise to careful, regional-level policies to support adaptation to changing weather.